Rubredoxin 1 Is Required for Formation of the Functional Photosystem II Core Complex in Arabidopsis thaliana - Che, Liping; Meng, Han; Ruan, Junxiang; Peng, Lianwei; Zhang, Lin (Frontiers in Plant Science, 2022)
Chloroplast thylakoid protein rubredoxin 1 (RBD1) in Chlamydomonas and its cyanobacterial homolog RubA contain a rubredoxin domain. These proteins have been proposed to participate in the assembly of photosystem II (PSII) at early stages. However, the effects of inactivation of RBD1 on PSII assembly in higher plants are largely unclear. Here, we characterized an Arabidopsis rbd1 mutant in detail. A drastic reduction of intact PSII complex but relatively higher levels of assembly intermediates including PSII RC, pre-CP47, and pre-CP43 were found in rbd1. Polysome association and ribosome profiling revealed that ribosome recruitment of psbA mRNA is specifically reduced. Consistently, in vivo protein pulse-chase labeling showed that rates of D1/pD1 synthesis and pD1 processing are significantly reduced in rbd1 compared with WT. Moreover, newly synthesized mature D1 and pD1/D2 can assemble into the PSII reaction center (RC) complex but further formation of larger PSII complexes is nearly totally blocked in rbd1. Our data imply that RBD1 is not only required for the formation of a functional PSII RC during early stages of PSII assembly but may be also involved in translation of D1 in higher plants.